Epidemiology of human brucellosis in military hospitals in Jordan: A five-year study - Maha Al-Amr; Lamees Abasi; Rame Khasawneh; Shirin Almharat; Ruba Al-Smadi; Nabeeha Abbasi; Osama Rabadi; Raida Oudat (Journal of Infection in Developing Countries)
Introduction: Brucellosis is a zoonotic disease with significant impacts on livestock and human health. It is a severe community health burden in the Middle East with an estimated 2000 times higher prevalence than in North America and Western Europe. To date, there are limited studies on human brucellosis and risk factors for infection in Jordan. Our study aimed to analyze documented brucellosis cases in Jordan and use geographic and socio-demographic data to better understand its prevalence and transmission.